Pearl millet: A befitting crop for the changing climate - Jacob, Jinu; Reddy, P Sanjana; Visarada, K B R S; Malathi, V M; Venkateswarlu, R (Indian Farming, 2023)
As per reports, global climate change might cause an increase in temperature up to 6°C by the end of 21st century which is feared to directly affect productivity of crop plants and food supply all over the world. The damage is more when temperature increase is in combination with various other kinds of biotic and abiotic stress factors. Crops that perform better under adverse and less favourable environmental conditions are the way out and pearl millet is a crop that fits in perfectly. It is a nutrient rich and climate resilient crop that can ensure increased income as well as food and nutritional security to the farming populations in arid and semi-arid regions of the globe.